Role of job and personal resources in the appraisal of job demands as challenges and hindrances. - Zofia Mockałło; Maria Widerszal-Bazyl (PLoS ONE, 2021)
Previous research has shown that challenge and hindrance job demands show different effects on employees' wellbeing and performance. Moreover, it has been demonstrated that employees' subjective appraisal of job demands as challenges and hindrances may vary: they can be appraised as challenges or hindrances or both. Subjective appraisal of job demands was found to be also related to employees' wellbeing and productivity. However, little is known about predictors of the appraisals of job demands made by employees. The aim of the study was to identify predictors of such appraisals among job and individual resources. Cross-sectional research was carried out among 426 IT, healthcare and public transport employees. COPSOQ II scales were used to measure job demands (emotional, quantitative, cognitive demands, work pace and role conflicts) and job resources (influence at work, possibilities for development, vertical and horizontal trust), single questions were used to measure employees' subjective appraisals of job demands as hindrances and challenges, and PCQ was used to measure psychological capital. Multiple hierarchical regression analyses showed that only horizontal trust predicted the appraisal of job demands as challenges, and vertical trust predicted the appraisal of job demands as hindrances among four analysed job resources. Individual resource-psychological capital-predicted only the appraisal of job demands as challenges. Control variables-occupation, age and job demands also played a significant role in predicting the appraisal of job demands. Implications and future directions are discussed.